GENDER NEUTRALISATION AND GENDER SPECIFICATION IN ENGLISH AND UZBEK LANGUAGES - Nurulloyeva Charos Ubaydullayevna. (TADQIQOTLAR.UZ, 2024)
Abstract. This article discusses such issues as the essence of the concept of gender, the definitions given to the concepts of gender and gender, gender studies of world and Uzbek scientists, the meaning of gender today, gender-neutral language and its importance.